Discrepancies between concentric and eccentric muscle actions strength - Ide, Bernardo Neme (2011)
The aim of this study was to observe the discrepancies between concentric and eccentric muscle actions strength in the tests of one repetition maximum concentric (1RMcon) and one repetition maximum eccentric (1RMexc) for the bench press (BP), Leg Press 45 ° (LP), and Seated Cable Rows (RC). Participated in the study 16 healthy young adults (9 men - age = 23.4 ± 3 years, mass = 74.2 ± 9.9 kg, height = 1.76 ± 0.06m.7 women - age = 25.4 ± 1.5 years, mass = 60.5 ± 9.1KG, height = 1.67 ± 0.06m). 1RMcon and 1RMexc loads were verified in 2 distinct sessions, and separated by one week each. Statistical analysis was performed using a two-way ANOVA with post test Tukey and Kramer multiple comparison test was adopted as a benchmark significant p <0.05. We observed that the 1RMexc loads were significantly higher (p <0.01) than those of 1RMcon in the 3 exercises analyzed. For the LP the difference was 53%, for the BP 70%, and the RC 62% higher. The observed data supported our hypothesis and further emphasize the importance of distinguishing the intensity used for the eccentric muscle actions in strength training.